Genome-wide comparative analysis of the nucleotide-binding site-encoding genes in four Ipomoea species - Si, Zengzhi; Wang, Lianjun; Qiao, Yake; Roychowdhury, Rajib; Ji, Zhixin; Zhang, Kai; Han, Jinling (Frontiers in Plant Science, 2022)
The nucleotide binding site (NBS) encoding genes is major type of resistance (R) genes, and its diverse evolutionary patterns were analyzed in different angiosperm lineages. Until now, no complete studies have been done on the NBS encoding genes in Ipomoea species. In this study, various numbers of NBS-encoding genes were identified across the whole the genome of sweet potato (I. batatas) (#889), I. trifida (#554), I. triloba (#571) and I. nil (#757). Gene analysis showed that the CN-type and N-type were more common than the other types of NBS-encoding genes. The phylogenetic analysis revealed that the NBS-encoding genes formed three monophyletic clades: CNL, TNL and RNL, which were distinguished by amino acid motifs. The distribution of the NBS-encoding genes among the chromosomes was nonrandom and uneven, 83.13, 76.71, 90.37 and 86.39% of the genes occurred in clusters in sweet potato, I. trifida, I. triloba and I. nil, respectively. The duplication pattern analysis reveals the presence of higher segmentally duplicated genes in sweet potato than tandemly duplicated ones. The opposite trend was found for the other three species. A total of 201 NBS-encoding orthologous genes were found to form synteny gene pairs between any two of the four Ipomea species, suggesting that each of the synteny gene pairs derived from a common ancestor. The gene expression patterns were acquired by analyzing by using the published datasets. Further analysis to explore the candidate resistant genes in sweet potato, transcriptome analysis has been carried out using two resistant (JK20, JK274) and susceptible cultivars (Tengfei, Santiandao) of sweet potato for stem nematodes and Ceratocystis fimbriata pathogen, respectively. A total of 11 differentially expressed genes (DEGs) were found in Tengfei and JK20 for stem nematodes and 19 DEGs in Santiandao and JK274 for C. fimbriata. Moreover, six DEGs were further selected for qRT-PCR analysis, and the results were consistent with the transcriptome analysis. The results may provide new insights into the evolution of NBS-encoding genes in the Ipomoea genome and contribute to the future molecular breeding of sweet potato.